2013
DOI: 10.1111/jasp.12125
|View full text |Cite
|
Sign up to set email alerts
|

I don't believe but I pray: spirituality, instrumentality, or paranormal belief?

Abstract: These three studies are among the first to systematically compare five Chinese religious groups on intrinsic (spiritual) and extrinsic (instrumental and paranormal) orientation. In Study 1, a Chinese version of the Index of Core Spiritual Experiences was developed. In Studies 2 and 3, spirituality and religious involvement was found to be greatest among Christians, followed in order by Buddhists, Taoists, traditional nones, and other nones. An instrumental purpose for religious activities and paranormal belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…In the Chinese cultural context, religious beliefs such as Buddhism, Taoism, or Christianity, traditional Chinese philosophies such as Confucianism and Daoism, which emphasize a tranquil, tolerant, and harmonious attitude towards life 48 , 49 , as well as spiritual seeking, can all serve as sources of support for individuals facing trauma. Family and social support emphasized in traditional Chinese culture, certain spiritual practices like meditation and prayer, as well as individuals’ perceptions and acceptance of destiny 31 , 32 , may contribute positively to post-traumatic growth. This correlation reflects the profound impact of cultural, belief, and societal factors on individual spiritual well-being, emphasizing the importance of considering spiritual factors within the context of cancer care and mental health practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Chinese cultural context, religious beliefs such as Buddhism, Taoism, or Christianity, traditional Chinese philosophies such as Confucianism and Daoism, which emphasize a tranquil, tolerant, and harmonious attitude towards life 48 , 49 , as well as spiritual seeking, can all serve as sources of support for individuals facing trauma. Family and social support emphasized in traditional Chinese culture, certain spiritual practices like meditation and prayer, as well as individuals’ perceptions and acceptance of destiny 31 , 32 , may contribute positively to post-traumatic growth. This correlation reflects the profound impact of cultural, belief, and societal factors on individual spiritual well-being, emphasizing the importance of considering spiritual factors within the context of cancer care and mental health practices.…”
Section: Discussionmentioning
confidence: 99%
“…While Chinese culture lacks formal religious development, philosophies like Buddhism, Taoism, and Confucianism have significantly shaped spiritual development and secular culture in China 28 . These philosophies instill resilience, embrace change, and encourage the pursuit of inner peace among the Chinese people 31 , 32 . Very few studies investigate the relationship between PTG and spiritual well-being in the Chinese context.…”
Section: Introductionmentioning
confidence: 99%
“…Taking Christianity as an example, in addition to the thirty million orthodox Christians in China, the other forty million Chinese citizens believe in the existence of Jesus or have participated in religious activities (Yang et al, 2007). Shiah, Chang, Tam, Chuang, and Yeh (2013) also found that most nonbelievers in China endorsed certain traditional Chinese religious beliefs or paranormal ideas.…”
Section: Introductionmentioning
confidence: 91%
“…Dibandingkan dengan para penganut barat, penganut Tao dan Budha memiliki ketertarikan yang lebih kuat dalam hal kegiatan dan kepercayaan terhadap agama (Shiah et al, 2013;Davidescu et al, 2022) Schneider, 2011).…”
Section: Perspektif Budha Dalam Perpajakanunclassified